Program pembinaan keislaman pendidik dan tenaga kependidikan di Sekolah Dasar Muhammad Al-‘Unaizy - Manaf, Yunan Al- (Tawazun: Jurnal Pendidikan Islam, 2022)
Educators and education personnel in Islamic education are role models for every student. Teaching knowledge, training, researching, developing and educating students is a noble task. But what happens is just the opposite, educators and education personnel are often not in line with Islamic education and do things that should not be done. Therefore, it is necessary to have an Islamic development programme for educators and education personnel in Islamic schools so as to change deviant behaviours among educators and education personnel. The purpose of this research is to find out the Islamic development programme for educators and education personnel at Muhammad Al-’Unaizy Elementary School. The research method used is qualitative research with a qualitative-descriptive approach. The findings of this study are the existence of an Islamic development programme for educators and education personnel at Muhammad Al-’Unaizy Elementary School consisting of yaumiyah (daily), usbuiyah (weekly), syahriyah (monthly), and tsanawi evaluation activities (semesterly and annually) for educators as well as education personnel. The purpose of the programme is the creation of consistency in carrying out Islamic teachings, mastery of the basics of Islamic knowledge, the realisation of good moral habits, and positive changes in students and the quality of education. Keywords: Guidance Evaluation; Education Quality; Islamic Development Abstrak Pendidik dan tenaga kependidikan dalam pendidikan Islam merupakan sosok teladan bagi setiap murid. Mengajarkan ilmu pengetahuan, melatih, meneliti, mengembangkan, dan mendidik para murid merupakan tugas mulia. Namun yang terjadi justru sebaliknya, pendidik dan tenaga kependidikan sering tidak sejalan dengan pendidikan Islam dan melakukan hal yang tidak semestinya dilakukan. Karenanya, perlu adanya program pembinaan keislaman untuk pendidik dan tenaga kependidikan di lingkungan Sekolah Islam sehingga mengubah perilaku-perilaku menyimpang di kalangan pendidik dan tenaga kependidikan. Tujuan dari penelitian ini adalah untuk mengetahui program pembinaan keislaman pendidik dan tenaga kependidikan di Sekolah Dasar Muhammad Al-‘Unaizy. Metode penelitian yang digunakan adalah penelitian kualitatif jenisnya penelitian lapangan dengan pendekatan kualitatif-deskriptif. Hasil temuan dari penelitian ini adalah adanya program pembinaan keislaman pendidik dan tenaga kependidikan di Sekolah Dasar Muhammad Al-‘Unaizy terdiri dari kegiatan yaumiyah (harian), usbuiyah (mingguan), syahriyah (bulanan), dan kegiatan evaluasi tsanawi (per semester dan tahunan) bagi pendidik juga tenaga kependidikan. Tujuan dari program tersebut yaitu terciptanya keistiqamahan dalam menjalankan ajaran Islam, penguasaan dasar-dasar ilmu keislaman, terwujudnya kebiasaan akhlak yang baik, dan perubahan positif terhadap peserta didik dan kualitas pendidikan.